Methods of Dendroindication of Developing Rapid Geomorphic Processes: An Overview - S. Nikolaeva A.; D. Savchuk A.; С. Николаева А.; Д. Савчук А. (Izvestiya Rossiiskoi akademii nauk. Seriya geograficheskaya, 2020)
Since the beginning of the 21st century dendrogeomorphological research are abruptly activated in Western Europe but are appreciable reduced in Russia. In the present foreign literature, the new methods and approaches of dendrogeomorphological research has been developed and discussed. The article goal is an overview of the dendrogeomorphological methods for identifying, dating and reconstructing the geomorphic events (debris flows, avalanches, rockfalls), their advantages and limitations at different stages of a dendro-geomorphological study. The dendrogeomorphological research are based on the J. Shroder’s “process— event-response” concept. The disputable questions and unsolved issues of the dendrogeomorphology are considered. С начала XXI в. дендроиндикационные исследования экзогенных гравитационных процессов (ЭГП) в Западной Европе резко активизировались, а в России, наоборот, значительно сократились. В современной зарубежной литературе по этой тематике разрабатываются новые подходы и методы исследования обусловленных ЭГП явлений на склоне, различные аспекты которых продолжают обсуждаться. Дан краткий обзор дендроиндикационных методов выявления, датирования и реконструкции обусловленных ЭГП явлений в прошлом (сели, лавины, обвалы/камнепады) на разных этапах дендрогеоморфологического исследования. Эти исследования основаны на концепции Дж. Шродера: “процесс—событие—отклик”. Как результат, выполнялись пространственно-временные реконструкции склоновых явлений на конкретных участках, т.е. оценка протяженности, частоты явлений и интенсивности процесса. Рассматриваются преимущества и ограничения методов, слабо разработанные или нерешенные проблемы дендроиндикации.